Impact of Covid-19 on Economic Indicators of Globalization: Evidence from Emerging and Developing Economies - Ashimosi, Gina Achitsa (University of the Witwatersrand, Johannesburg, 2023)
This study analyzed the impact that the iCOVID-19 pandemic has on two important economic indicators of globalization, namely: bilateral trade flows and Foreign direct investment. This thesis used the trade gravity model, estimated using the Poisson Pseudo Maximum likelihood (PPML), to look at the influence of COVID-19 cases and death counts on bilateral trade. For foreign direct investment, this paper used a panel data analysis to establish the influence of iCOVID-19 cases and death counts have on FDI. The study finds a negative relationship between bilateral trade and iCOVID-19 cases and death counts for both country of origin and destination country. trade agreements, official language, contiguity and GDP have a positive influence on bilateral trade for both trading partners. When estimations are done using foreign direct investment (FDI) as dependent variable, real GDP is positively associated with FDI flows, the exchange rate is positive but to significant, while unemployment is negative but not significant as well. The 2020 dummy variable is negative and significant, thus FDI flows were adversely affected during that year compare to other years. consequently, the study found that the iCOVID-19 pandemic has had a significant impact on the two most important economic indicators of globalization international trade and FDI. some of the recommendations are that there should be a reduction in tariffs among countries to foster bilateral trade and i also diversification of commodities so that a country does not just rely ion one commodity as that would impact them negatively in a pandemic.
A research report submitted partially fulfillment the requirements for the degree of Master of Management in Finance & Investments to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Bilateral itrade; FDI; Covid-19 pandemic; exchange rate; Gravity model; UCTD; SDG-8: Decent work and economic growth